Genome-Wide Prediction, Functional Divergence, and Characterization of Stress-Responsive BZR Transcription Factors in B. napus - Sarwar, Rehman; Geng, Rui; Li, Lei; Shan, Yue; Zhu, Ke-Ming; Wang, Jin; Tan, Xiao-Li (Frontiers in Plant Science, 2022)
BRASSINAZOLE-RESISTANT (BZR) are transcriptional factors that bind to the DNA of targeted genes to regulate several plant growth and physiological processes in response to abiotic and biotic stresses. However, information on such genes in Brassica napus is minimal. Furthermore, the new reference Brassica napus genome offers an excellent opportunity to systematically characterize this gene family in Brassica napus. In our study, 21 BnaBZR genes were distributed across 19 chromosomes of Brassica napus and clustered into four subgroups based on Arabidopsis thaliana orthologs. Functional divergence analysis among these groups evident the shifting of evolutionary rate after the duplication events. In terms of structural analysis, the BnaBZR genes within each subgroup are highly conserved but are distinctive within groups. Organ-specific expression analyses of BnaBZR genes using RNA-seq data and quantitative real-time polymerase chain reaction (qRT-PCR) revealed complex expression patterns in plant tissues during stress conditions. In which genes belonging to subgroups III and IV were identified to play central roles in plant tolerance to salt, drought, and Sclerotinia sclerotiorum stress. The insights from this study enrich our understanding of the Brassica napus BZR gene family and lay a foundation for future research in improving rape seed environmental adaptability.